New Species of Lentaria (Fungi: Aphyllophorales): redescription and mating systems of L. surculus and L. byssiseda - Petersen, Ronald H. (Revista de Biología Tropical, 2000)
The following names are proposed for species of Lentaria new lo science: L. boletosporioides from New Zealand with stout basidiomata and boletoid basidiospores; L. caribbeana from Caribbean islands and circum- Caribbean landmasses, with large basidiomata and large basidiospores; L. glaucosiccescens froro New Zealand, with basidiomata tuming grey-green upon drying; and L. rionegrensis from Argentina, with densely branched, ruddy basidiomata. Lentaria javanica nomo nov. ís proposed to substitute for Clavaria compressa, a later homonym. Basidiospore statistics indicate infraspecific differentiation within L. surculus and two morphological variants are described. Lentaria surculus and L. byssiseda exhibit tetrapolar roating systems, and the two species are sexually interincompatible